Minorités linguistiques et culturelles à l'avant-garde de l'interculturalité nord/sud : quelles potentialités à partir de l’exemple corse ? - Claude Cortier; Alain Di Meglio (Multilinguales)
The geographical position of Corsica makes of it a crossroads between northern and southern shores of the Mediterranean area. This evocation, often of a fantasy order has not fed at least an amount of work, actions and thoughts in various areas of the Corsican society.How is Corsica, with other regions, seeking to enroll in a managed and valued diversity that breaks an obsolete dichotomy between single dominant public culture and non-recognized minority cultures ? What kind of model is it searching for in order to avoid the trap of nation-states mirror ? According to its critical apparatus or its quest for a new model, could it have a southern shore value, sharing more or less issues related to post-colonial situations, conflictingacculturation situations ? Regarding the question of culture in Corsica and the presentation of a number of experiments and research in the educational system, we tried to identify transposable potential an alternative cultural model where pains, conflicts or tensions related to historical situations could be overcome by taking into account the cultural complexity and an opened up management of diversity.